STUDIES ON WATER QUALITY OF KELEWADI LAKE IN RELATION TO PISCICULTURE, MAHARASHTRA - PAWAR, B.A.; PANDARKAR, A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Changes in water quality parameters (physico-chemical) of a rain fed Kelewadi lake at Kelewadi village, near Bota, Sangamner taluka, Ahmednagar district were investigated to assess the suitability of this lake for pisciculture. Several parameters viz., temperature, dissolved oxygen (DO), pH, total alkalinity, chloride, hardness, calcium, magnesium, nitrite and phosphate have been studied for a period of one year beginning from February 2008 to January 2009. All the physico-chemical parameters determined, revealed that the fluctuations in water temperature, dissolved oxygen, pH, total alkalinity, hardness and nitrite in all the seasons and magnesium during summer and phosphate during post-monsoon to summer were with in the desirable limits for fish and fisheries practices. However, low level of chloride and calcium in all the seasons and magnesium in monsoon to winter and high level of phosphate during monsoon were recorded. These parameters need to be modifying in order to favour fish culture.